Thor - tribble42 (Zenodo, 2016)
This is a scan of my copy of the Eyrarland Statue which allegedly depict the god Thor. This small statue was sculpted approximately 1000 years ago. It was found in Akureyri, Iceland and currently reside in the National Museum of Iceland. ![](http://media.offexploring.co.uk/photos/ambrosial-adventures/photos/100113010810-thumbnail_IMG_5054.jpg) Source: Objaverse 1.0 / Sketchfab